Genetic differentiation and evolutionary history of the circumpolar species Ophiura sarsii and subspecies Ophiura sarsii vadicola (Ophiurida: Ophiuridae). (1st June 2020) - Li, Yixuan; Dong, Yue; Xu, Qinzeng; Fan, Shiliang; Lin, Heshan; Wang, Minghui; Zhang, Xuelei
Abstract: Brittle stars are dominant species in diverse benthic communities. As a circumpolar ophiuroid, Ophiura sarsii is distributed from Arctic waters to north temperate zones. The subspecies O. sarsii vadicola is dominant in the benthic communities of the Sea of Japan and the Yellow Sea Cold Water Mass (YSCWM). It lives at the southernmost boundary of O. sarsii distribution. Little is known about the genetic relationships of the different O. sarsii populations. We studied the molecular diversity, genetic divergences and demographic changes among seven O. sarsii populations from the north Pacific to the Atlantic, and O. sarsii vadicola from the YSCWM using the mitochondrial cytochrome c oxidase subunit I gene ( CO I ). Based on COI data, three lineages were determined among the eight geographic populations. O. sarsii vadicola is an independent mitochondrial lineage that maintains its subspecies status based on Internal transcribed Spacer 2 ( ITS 2 ) data. The differentiation between species and subspecies may have occurred in the Sea of Japan at 3.6 million years ago (Ma) during the late Pliocene. O. sarsii may have dispersed from the Pacific to the Atlantic Ocean since early Pleistocene (1.5–1.2 Ma). The expansion of the subspecies was likely coeval with transgressions events in the Yellow Sea during the late Pleistocene period (111.8–60.1 ka). Additional samples and molecular markers from different areas of the O. sarsii distribution will be needed to unravel the evolutionary history of this species. Highlights: The divergence between Ophiura sarsii and subspecies O. sarsii vadicola occurred at 3.6 Ma. Pacific individuals of O. sarsii dispersed to Atlantic Ocean since early Pleistocene. O. sarsii vadicola population expanded at 111.8–60.1 ka in the ancient Yellow Sea.